Impact of healthy lifestyle on physical fitness among school-aged children: A comparative study between Indonesia and Pakistan - Sulistiyono, Sulistiyono; Prastyawan, Rifky Riyandi; Arjuna, Fatkurahman; Nugroho, Sigit; Salman, Muhammad (MEDIKORA, 2025)
Children's general well-being is greatly influenced by physical fitness and leading a healthy lifestyle, although there are differences depending on the sociocultural context. The objective is to examine how healthy lifestyle choices affect school-age children's levels of physical fitness in Pakistan and Indonesia. The study provides valuable insights for educators, health practitioners, and policymakers to design strategies that promote healthier behaviours among children in diverse cultural settings. Methods: Researchers conducted cross-sectional research comparing 375 junior high school pupils from Pakistan (n = 182) and Indonesia (n = 193). The Multistage Fitness Test (MFT) was used to measure physical fitness levels, and a healthy living questionnaire was used to collect data. To assess the differences between the two groups, statistical analyses were conducted using independent sample t-tests, homogeneity tests, and normality tests. Result: The homogeneity and normality tests confirmed that the data were suitable for parametric analysis. The two groups' levels of physical fitness (t = 3.431, p = 0.000) and healthy lifestyle (t = 4.059, p = 0.000) differed significantly, according to the independent sample t-test. Compared to their Pakistani counterparts, Indonesian students demonstrated greater levels of physical fitness and a healthier lifestyle. These results suggest that students' fitness levels and lifestyle choices may be influenced by sociocultural, environmental, and educational conditions.Conclusion: Compared to Pakistani students, Indonesian students demonstrate greater levels of physical fitness and healthier lifestyle choices, underscoring the need for focused interventions to enhance the well-being of children in both nations. These findings can help schools, community organisations, and public health authorities develop targeted programs to foster healthy habits and improve youth fitness across different sociocultural contexts. Future studies ought to investigate the root reasons for these disparities and create policies that encourage students in various sociocultural contexts to lead healthier lives. Keywords: Children of School age, Indonesia, Pakistan, Healthy Lifestyle, Physical Fitness.